Leadership Style of Student Production House Organization (Case Study on Label N) - Ichsan Adil Prayogi; Erika Yulianti (Jurusan Ilmu Komunikasi UTM, 2023)
The research is based on finding out how the leadership style of a production house founded by college students named Label N. This research uses a qualitative method with a case study approach. Qualitative research with a case study approach seeks to describe data in words or sentences separated by categories to obtain conclusions. Sources of data were collected through in-depth interviews regarding the leadership style applied by Label N. In the leadership style, Label N tries to establish a democratic leadership style. However, this democratic leadership style which is similar to the